RANCANG BANGUN PERILAKU BUATAN PADA NON-PLAYER CHARACTER DALAM GAME PEMADAM KEBAKARAN MENGGUNAKAN FINITE STATE MACHINE DAN GODOT SCRIPT - Wiriasto, Giri Wahyu; Fikriansyah, Muhammad; Rachman, A. Sjamsjiar (DIELEKTRIKA, 2023)
The application of artificial behavior in the object character of a game that is played using a computer device continues to grow. The implementation of the algorithm in the game makes game object characters that can move autonomously according to changes in scenario roles making the game more attractive to human players. This autonomous computer player behavior is known as a non-player character (NPC). In this research a game has been developed in the category of role-playing game (RPG) which is called the Fire Extinguisher Game. In this game there is an NPC character "fire monster" as an antagonist whose mission is to defeat the human player as the protagonist by burning all the objects in the scene role scenario. In order to make it clear and to make it easier to develop NPC player behavior designs, the Finite State Machine (FSM) method and godot script programming are used. The FSM method describes the behavior design of each NPC character in the form of states, where these will change according to the interactions that occur between players in the scene of the game environment. In its implementation, there are test parameters that are used, so that it can be shown that this game has successfully played. This game runs on a desktop and has tested using the black-box testing method to get a functional performance test. The results of this research are the design of artificial behavioral events on NPCs using the godot script code approach.